2013
DOI: 10.1016/j.neuroimage.2013.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic connectivity network mapping in young children during natural sleep

Abstract: Structural and functional neuroimaging have substantively informed the pathophysiology of numerous adult neurological and psychiatric disorders. While structural neuroimaging is readily acquired in sedated young children, pediatric application of functional neuroimaging has been limited by the behavioral demands of in-scanner task performance. Here, we investigated whether functional magnetic resonance imaging (fMRI) acquired during natural sleep and without experimental stimulation offers a viable strategy fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Several studies have demonstrated that young children at similar ages were reliably found to be in non-rapid eye movement sleep stage 3 (NREM3) within this time frame. 30-32 …”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated that young children at similar ages were reliably found to be in non-rapid eye movement sleep stage 3 (NREM3) within this time frame. 30-32 …”
Section: Methodsmentioning
confidence: 99%
“…Sleep has been successfully used in pediatric populations to achieve in-scanner immobility for anatomical MRI [Giedd et al, 1999], task-activation fMRI (using auditory stimuli) [Anderson et al, 2001;Redcay and Courchesne, 2008], and during resting-state fMRI [Manning et al, 2013]. In prior work from our laboratory, we demonstrated that intrinsic connectivity networks (ICNs) persist during natural, nocturnal sleep in pre-school-aged neurotypical children [Manning et al, 2013].…”
Section: Introductionmentioning
confidence: 96%
“…Resting‐state fMRI, however, is notoriously susceptible to movement artifacts [Power et al ], which poses a substantial obstacle for pediatric studies, in general, and for pediatric brain injury, in particular. Sleep has been successfully used in pediatric populations to achieve in‐scanner immobility for anatomical MRI [Giedd et al, ], task‐activation fMRI (using auditory stimuli) [Anderson et al, ; Redcay and Courchesne, ], and during resting‐state fMRI [Manning et al, ]. In prior work from our laboratory, we demonstrated that intrinsic connectivity networks (ICNs) persist during natural, nocturnal sleep in pre‐school‐aged neurotypical children [Manning et al, ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations